Rediscovering mathematics : you do the math - Simonson, Shai (Classroom resource materials (Unnumbered), 2011)
Rediscovering mathematics is an eclectic collection of mathematical topics and puzzles aimed at talented youngsters and inquisitive adults who want to expand their view of mathematics.--